Analysis of CPS (Country Partnership Strategy) Conformity to Vietnam of Korean ODA Projects - et al., Young-Chool Choi (International Journal of Advanced Science and Technology, 2020)
This study was conducted in recognition of a problem, namely that ODA (Official DevelopmentAssistance) projects organised by the donor country, and the detailed Country Partnership Strategy(CPS) targets established for the recipient country, were not in good agreement. The underpinnings ofthis study are as follows. First, the problem with Korea’s CPS for Vietnam is that its performanceobjectives are too abstractly presented, and therefore not enough to serve as a guideline. Second,some of Korea’s CPS targets for Vietnam (e.g. the transportation target) are not supported by anyproject. This may be said to be a problem, whether the initial creation of the CPS was wrong orinsufficient review was made when deciding on aid projects for Vietnam. Third, among the CPStargets for Vietnam, the inclusiveness target (vulnerable class and social integration support) issupported by the largest number of projects, so the match between the project and the target is thestrongest. Overall, since the Korean CPS for Vietnam is abstract, it is necessary to determine whichprojects have low consistency by applying methods such as social network analysis to increase theconsistency of individual projects. In order to solve these problems, we believe that social networkanalysis methods can be efficacious.